THE SIGNIFICANCE OF ISLAMIC SOCIAL FINANCE IN STABILISING INCOME FOR MICRO-ENTREPRENEURS DURING THE COVID-19 OUTBREAK - Nik Hadiyan Nik Azman; Tajul Ariffin Masron; Haslindar Ibrahim (Journal of Islamic Monetary Economics and Finance, 2021)
The COVID-19 pandemic has heavily impacted micro-entrepreneurs worldwide. Some need to remain open to survive; some need to shift employees to remote work, and some need to shut down to save cost. Although there is an incentive and assisting funds given by the government, the fund might only last for three months. The funds might be accessed through Islamic Social Finance tools (Zakat, Waqf, Baytulmal, Ar-Rahnu). ISF is assisting and supporting micro-entrepreneurs to survive. Although ISF mitigates the risk by providing fund assistance to micro-entrepreneurs, it is essential to know how far this assistance can further backing them to survive in doing business. Therefore, this study intends to investigate the significance of social finance in Islamic ways to stabilize micro-entrepreneurs' income during the COVID-19 pandemic. A survey consists of 200 questionnaires distributed to micro-entrepreneurs in three states in Malaysia between June to August 2020. The finding shows that ISF plays an essential role in stabilizing income among micro-entrepreneurs during pandemic COVID-19.